Recherche agronomique et politique agricole - Valceschini, Egizio; Maeght-Bournay, Odile; Cornu, Pierre (éditions Quae, 2019)
Father of animal genetics in France and of the 1966 law on livestock farming, in 1978 Jacques Poly signed the report entitled 'Towards a more economical and autonomous agriculture', coinciding with his becoming an executive manager of INRA. Based on the juxtaposition of the testimony of those who were active at that time and the work of historians, this book is an exploration of his extraordinary trajectory.